Local but not long-range microstructural differences of the ventral temporal cortex in developmental prosopagnosia. (November 2015) - Song, Sunbin; Garrido, Lúcia; Nagy, Zoltan; Mohammadi, Siawoosh; Steel, Adam; Driver, Jon; Dolan, Ray J.; Duchaine, Bradley; Furl, Nicholas
Abstract: Individuals with developmental prosopagnosia (DP) experience face recognition impairments despite normal intellect and low-level vision and no history of brain damage. Prior studies using diffusion tensor imaging in small samples of subjects with DP ( n =6 or n =8) offer conflicting views on the neurobiological bases for DP, with one suggesting white matter differences in two major long-range tracts running through the temporal cortex, and another suggesting white matter differences confined to fibers local to ventral temporal face-specific functional regions of interest (fROIs) in the fusiform gyrus. Here, we address these inconsistent findings using a comprehensive set of analyzes in a sample of DP subjects larger than both prior studies combined ( n =16). While we found no microstructural differences in long-range tracts between DP and age-matched control participants, we found differences local to face-specific fROIs, and relationships between these microstructural measures with face recognition ability. We conclude that subtle differences in local rather than long-range tracts in the ventral temporal lobe are more likely associated with developmental prosopagnosia. Highlights: Developmental prosopagnosics ( n =16) show white matter deficits local to FFA. Fractional anisotropy in WM local to FFA correlates with face identity recognition. Contrary to prior reports, long-range tracts (IFOF and ILF) in DP appear normal. Findings are additional evidence that DP often involves posterior regions.